Self-reported dependence on mobile phones in young adults: a European cross-cultural empirical survey - Lopez-Fernandez, O; Kuss, DJ; Romo, L; Morvan, Y; Kern, L; Graziani, P; Rousseau, A; Rumpf, H-J; Bischof, A; Gassler, A-K; Schimmenti, A; Passanisi, A; et al. (2017)
Background and aims: Despite many positive benefits, mobile phone use can be associated with harmful and detrimental behaviors. The aim of this study was twofold: to examine (a) cross-cultural patterns of perceived dependence on mobile phones in ten European countries, first, grouped in four different regions (North: Finland and UK; South: Spain and Italy; East: Hungary and Poland; West: France, Belgium, Germany, and Switzerland), and second by country, and (b) how socio-demographics, geographic differences, mobile phone usage patterns, and associated activities predicted this perceived dependence. Methods: A sample of 2,775 young adults (aged 18-29 years) were recruited in different European Universities who participated in an online survey. Measures included socio-demographic variables, patterns of mobile phone use, and the dependence subscale of a short version of the Problematic Mobile Phone Use Questionnaire (PMPUQ; Billieux, Van der Linden, & Rochat, 2008). Results: The young adults from the Northern and Southern regions reported the heaviest use of mobile phones, whereas perceived dependence was less prevalent in the Eastern region. However, the proportion of highly dependent mobile phone users was more elevated in Belgium, UK, and France. Regression analysis identified several risk factors for increased scores on the PMPUQ dependence subscale, namely using mobile phones daily, being female, engaging in social networking, playing video games, shopping and viewing TV shows through the Internet, chatting and messaging, and using mobile phones for downloading-related activities. Discussion and conclusions: Self-reported dependence on mobile phone use is influenced by frequency and specific application usage.